Analisis Pelaksanaan Tindak Lanjut Rekomendasi BPK dari Perspektif Teori Edwards III (Kasus pada Kabupaten X di NTT) - Blegur, Ronal; Irianto, Gugus; Rosidi, Rosidi (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2017)
The aim of this research is to analyze the implementation of following up BPK recommendation on the finding of examinations results which still have occurred repeatedly from the Edwards III perspective. Qualitative descriptive approach is chosen to obtain the depth of information. The results showed that the implementation of follow-up is not optimal because the communication has not run well, the resources including staff, information, authority and facilities are not yet adequately available, not all implementers have good attitudes in the implementation of follow-up indicated by low commitment. Besides that, the OPD does not have SOP for budget execution, BKAD as SKPKD and Regional Inspectorate as APIP does not have SOP implementation of follow-up of BPK recommendation which involving OPD.The result of the research shows that Alor regency government organization structure which has been well regulated according to Local Regulation number 8 year 2016 is expected to be a supporting factor in the implementation of government activities such as follow-up of BPK's recommendation.